Social media as a local political arena: the strategies of Padang legislators in building connections with netizens - Sumartono,; Salman M. Noer,; Doddie Arya Kusuma B.,; Yumi Ariyati, (Technium Social Sciences Journal, 2025)
This study explores how legislators in the city of Padang have innovatively utilized social media to engage with their constituents. Twelve informants were involved, consisting of six Padang legislators and six netizens who follow them on social media. The study employed a phenomenological approach using qualitative methods such as observation, in-depth interviews, and literature review. The findings show that social media facilitates two-way communication, allowing constituents to interact directly with legislators and receive immediate responses to community issues. Two key aspects of the legislators’ social media strategies were identified: how they define “friends” and “friendship” with netizens, and how they manage their online presence. Social media serves as a platform for legislators to showcase their performance, while also functioning as a tool for netizens to assess it. Furthermore, legislators tailor their use of social media platforms: WhatsApp is used for close contacts, Facebook and Instagram to reach the general public, and TikTok to engage with millennials. A clear distinction is also made between personal and official posts to ensure transparency and appropriateness in their online interactions.